2015
DOI: 10.1038/aps.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem augments the influence of MDR1 genotype status on cyclosporine concentration in Chinese patients with renal transplantation

Abstract: Aim: Co-administration of diltiazem can reduce the dosage of cyclosporine (CsA) in patients with renal transplantation. In this study, we investigated how diltiazem altered the relationship between MDR1 genetic polymorphisms and CsA concentration in Chinese patients with renal transplantation. Methods: A total of 126 renal transplant patients were enrolled. All the patients received CsA (2-4 mg·kg -1 ·d -1 ), and diltiazem (90 mg/d) was co-administered to 76 patients. MDR1-C1236T, G2677T/A, and C3435T polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Several other studies have also reported correlations between MDR1 gene polymorphisms and cyclosporine and tacrolimus concentrations. [15][16][17][18] In the present study, the incidence of grade II-IV acute GVHD and CMV viral load was higher in the MDR1 G2677TA matched group compared to the mismatched group. However, these observations did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 46%
“…Several other studies have also reported correlations between MDR1 gene polymorphisms and cyclosporine and tacrolimus concentrations. [15][16][17][18] In the present study, the incidence of grade II-IV acute GVHD and CMV viral load was higher in the MDR1 G2677TA matched group compared to the mismatched group. However, these observations did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 46%
“…For example, cyclosporine is an ABCB1 substrate. Diltiazem (a moderate ABCB1 inhibitor [38]) has been shown to increase cyclosporin trough concentrations in Chinese patients who carry the TT genotype (low P-gp activity) at rs1045642 (C>T) in ABCB1; yet no effect was seen in other ABCB1 genotypes (e.g., CC at rs1045642) [39]. Methadone is also a P-gp substrate, acting in the brain and effluxed across the BBB via P-gp.…”
Section: Efflux Transportersmentioning
confidence: 99%
“…Whisker-reinforced composites, as composite materials with structure-function integration, have excellent electric conduction and microwave absorption. Moreover, the structural load-carrying capacity of whisker-reinforced composites can be potentially applied in high-tech industry, aerospace, aviation, and other fields [3][4][5].…”
Section: Introductionmentioning
confidence: 99%